Begomovirus evolution in the New World: Genetic variability of populations and its effect on speciation - Ramos Sobrinho, Roberto (2014)
Viruses belonging to the family Geminiviridae have circular ssDNA genomes and infect a broad range of plant species causing devastating diseases, mainly in subtropical and tropical countries. The family is divided into seven genera (Begomovirus, Becurtovirus, Curtovirus, Eragrovirus, Mastrevirus, Topocuvirus and Turncurtovirus) according to the type of insect vector, host range, genome organization and phylogeny. Begomoviruses are whitefly- transmitted and are among the most damaging pathogens causing epidemics in economically important crops worldwide. Wild/non-cultivated plants play a crucial epidemiological role, acting as begomovirus reservoirs and as "mixing vessels" where recombination can occur. Furthermore, previous results suggest that begomovirus populations in non-cultivated hosts are more genetically variable then those infecting cultivated hosts. Most New World (NW) begomoviruses have two genomic components designated as DNA-A and DNA-B, and their genomes have the capacity to evolve quickly via mutation, reassortment and recombination. In this context, this work aimed: (i) to assess the effect of the host on the standing genetic variability of begomovirus populations; and (ii) to study the effect of recombination on the evolution of New World begomoviruses. For the first objective, cultivated (common bean, Phaseolus vulgaris, and lima bean, P. lunatus) and non-cultivated (Macroptilium lathyroides) legume hosts were intensively sampled from two regions across Brazil between 2005 and 2012. A total of 212 full-length DNA-A components were cloned and sequenced, and populations of the begomoviruses Bean golden mosaic virus (BGMV) and Macroptilium yellow spot virus (MaYSV) were obtained from the three hosts. Our results indicate that the presumed genetic variability of the host did not affect viral variability. MaYSV (N = 99) showed higher genetic variability than BGMV (N = 147), with the BGMV (but not the MaYSV) population being structured based on both host and geography. For the second objective, datasets including all DNA-A and DNA-B reference sequences of NW begomoviruses were obtained from GenBank. Our analyses indicate that South American begomoviruses do not exhibit geographic monophyly, with evidence of at least two independent introduction events in this region. Recombination was detected as a very important evolutionary mechanism acting on DNA-A evolution. We found evidence of greater genetic variability in begomoviruses from Central America and the Caribbean compared to South America (SA). Additional introduction events may impact the evolution of begomoviruses in SA by favoring recombination and introducing new virulence features to indigenous South American begomoviruses.